Preventive Effects of Total Flavonoid C-Glycosides from Abrus mollis on Nonalcoholic Fatty Liver Disease through Activating the PPARα Signaling Pathway - Hu, Xiao-Long; Niu, Ya-Jun; Chen, Mi; Feng, Jia-Hao; Shen, Wei; Jiang, Zhen-Zhou; Zhang, Xiao-Qi; Ye, Wen-Cai; Xiong, Fei; Wang, Hao (Planta Medica, 2019)
Abrus pulchellus subsp. mollis (Hance) Verdc. (Leguminosae) is a well-known edible plant usually added to soups and beverages. In this study, vicenin-2 (1), isoschaftoside (2), schaftoside (3), and their enrichment fraction, total flavonoid C-glycosides, derived from the extracts of A. mollis, were firstly found to prevent nonalcoholic fatty liver disease both in vitro and in vivo. In the in vitro study, total flavonoid C-glycosides decreased the lipid accumulation in oleic acid-treated HepG2 cells. The mechanisms of total flavonoid C-glycosides are involved in the regulation of peroxisome proliferator-activated receptor α and its downstream, and the reduction of proinflammatory cytokines. In high-fat diet-induced fatty liver rats, total flavonoid C-glycosides decreased the levels of glutamic-oxalacetic transaminease and glutamic-pyruvic transaminase, and decreased the lipid accumulation both in the liver and blood without affecting food intake. In addition, total flavonoid C-glycosides also increased the activities of the antioxidant enzyme system in vivo. In conclusion, total flavonoid C-glycosides are active components of A. mollis on nonalcoholic fatty liver disease, and can be used in functional food and supplements for nonalcoholic fatty liver disease prevention and treatment.
Keywords: Nonalcoholic fatty liver disease; Abrus pulchellus subsp. mollis; total flavonoid C-glycosides; high-fat diet; PPARα